KONSTRUK KOMPETENSI LITERASI UNTUK SISWA SEKOLAH DASAR - Musfiroh, Tadkiroatun; Listyorini, Beniati (LITERA, 2016)
This study aims to: (1) describe the literacy components based on the PIRLS version, (2) identify the constructs of reading literacy competence for Grade IV of the elementary school, and (3) make a draft of the constructs of literacy competence for Grade IV of the elementary school in the Indonesian version. The data were collected through literature review, interviews, and focus group discussion. They were analyzed by the qualitative descriptive technique. The results are as follows. First, the literacy components based on the PIRLS version comprise: the reading literacy concept, assessment framework, benchmark, literary text components, and assessment system determination. Second, the reading literacy competence is constructed as the competence to read and comprehend literary and informative texts, based on four cognitive levels, from a variety of text types in line with the social context around the students and the national context. Third, the constructs of literacy competence in the Indonesian version consist of: 2-5 difficult words, a text length of 200 words, the composition of low to high cognitive levels of 30-30-3010, text themes suitable to Indonesian condition and culture, clear text illustrations, and tables/graphs presented in gradation. The results are important as literacy information for the basis for developing educational policies in Indonesia.